PENGELOLAAN SARANA LABORATORIUM BAHASA - Aprian Tanzili; Rambat Nur Sasongko; Sumarsih Sumarsih (UNIVERSITAS BENGKULU, 2018)
Abstract: The purpose of this study is to describe the management facility of language laboratory at Public Senior High School Number One Muara Pinang Empat Lawang District. The method of the study is descriptive qualitative. The objects are principle, vice principle of facility, head og language laboratory, laboran, language teacher and students. The techniques of the data are interview, observation, and documentation study. The conclusion shows that: The planning of the facility do in, the early of academic year but the committee seldom existed. The provisioning of the facility mostly by puchasing and the government assist. The inventories of the facility aren’t proceduraly. The storage of the facility are procedurally. The using of the facility unapropriate of the list of schedule but the regulation has been running well. The maintenance of the facility is doing based on necessity, the maintenance are; daily, regulary and intern of repairman. The cleaning out of the facility is never done, damaged facility are only warehoused. Keyword: Management language laboratory, Facility language laboratory.